Activation of tumor suppressor p53 gene expression by magnetic thymine-imprinted chitosan nanoparticles. Issue 10 (23rd December 2015) - Lee, Mei-Hwa; Thomas, James L.; Chen, Jian-Zhou; Jan, Jeng-Shiung; Lin, Hung-Yin
Abstract : Chitosan nanoparticles imprinted with thymine (and containing magnetic nanoparticles for ease in separations) were found to have dramatic effects on the expression of p53 in HepG2 cells. Abstract : Chitosan is a natural biodegradable polysaccharide that has been used to enhance gene delivery, owing to the ease with which chitosan nanoparticles enter the nucleus of cells. To study the effects of nuclear delivery of telomeric gene sequences, which contain thymine, we formed magnetic thymine-imprinted chitosan nanoparticles (TIPs) by the precipitation of chitosan, mixed with thymine and magnetic nanoparticles (to aid in separations). The mean size of the TIPS was 116 ± 18 nm; the dissociation constant for thymine was 21.8 mg mL −1 . We then treated human hepatocellular carcinoma (HepG2) with TIPs nanoparticles bearing bound thymine or a bound telomeric DNA sequence. The expression of the tumor suppressor p53 gene increased when TIPs were applied and decreased when telomere-bound TIPs were applied.